2003
DOI: 10.1111/j.1440-1746.2004.03253.x
|View full text |Cite
|
Sign up to set email alerts
|

Age as a predictor of hyperphosphatemia after oral phosphosoda administration for colon preparation

Abstract: Administration of OPS causes a significant rise in serum phosphate, even in patients with normal CCR. The elevation is significantly greater in elderly patients. Administration of OPS can be considered safe for young and middle-aged patients with normal renal function; however, it should be used with caution in elderly patients, even in those with normal CCR and serum creatinine values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 7 publications
1
35
0
6
Order By: Relevance
“…A larger study examined electrolyte changes in 143 patients who received OSPS and found a mean increase in serum phosphorus of 3 mg/dl and a mean decline in serum calcium of 0.3 mg/dl (5). A more recent study found that older patients achieve greater levels of hyperphosphatemia after use of OSPS (6). In particular, the mean increase in serum phosphorus after use of OSPS was 3.4 mg/dl in patients who were between 25 and 35 yr of age, compared with 5.5 mg/dl in individuals who were older than 56 yr (6).…”
Section: Discussionmentioning
confidence: 99%
“…A larger study examined electrolyte changes in 143 patients who received OSPS and found a mean increase in serum phosphorus of 3 mg/dl and a mean decline in serum calcium of 0.3 mg/dl (5). A more recent study found that older patients achieve greater levels of hyperphosphatemia after use of OSPS (6). In particular, the mean increase in serum phosphorus after use of OSPS was 3.4 mg/dl in patients who were between 25 and 35 yr of age, compared with 5.5 mg/dl in individuals who were older than 56 yr (6).…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, vários relatos da literatura têm referido elevações acentuadas nas dosagens de P sérico nos pacientes cujo preparo é realizado com a solução de NaP, incluindo um caso isolado de óbito associado a tal alteração (Miki Jr et al, 2002;Gumurdulu et al, 2004;Gonlusen et al, 2006). Essa condição não foi verificada nesse trabalho.…”
Section: Resultsunclassified
“…Gümürdülü ve ark. [6] tarafından ülkemizde yapılan, kreatinin klirensi 70 mL/dakikanın üzerinde 70 hastanın değerlendirildiği çalışmada, kolon hazırlığı için kullanılan NaP'ın serum elektrolit değerlerine etkisi incelenmiştir. NaP sonrası kalsiyum ve potasyum değerlerinde anlamlı düşme (p<0.05), fosfat ve sodyum değerlerinde ise anlamlı yükselme saptanmıştır (p≤0.01).…”
Section: Discussionunclassified
“…[1,2,[6][7][8][9][10] Ancak ileri yaş, hipertansiyon, yetersiz hidrasyon, ilaç kullanımı (ACE-İ, ARB, diüretik), bağırsak tıkanıklığı ve aktif kolit gibi risk faktörlerinin varlığında fosfat nefropatisi gelişme riskinin arttığı bilinmektedir. [2,6,7,11,12] Markowitz ve ark. [11] tarafından 2004 yılında yapılan bir çalışmada NaP kullanımı sonrasında nefrokalsinozis ve akut böbrek yetmezliği gelişimi olan 5 hasta incelenmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation